Exploring the Relationship between Brain Plasticity, Migratory Lifestyle, and Social Structure in Birds - Barkan, Shay; Yom-Tov, Yoram; Barnea, Anat (Frontiers in Neuroscience, 2017)
Studies in Passerines have found that migrating species recruit more new neurons into brain regions that process spatial information, compared with resident species. This was explained by the greater exposure of migrants to spatial information, indicating that this phenomenon enables enhanced navigational abilities. The aim of the current study was to test this hypothesis in another order - the Columbiformes –using two closely-related dove species - the migrant turtle-dove (Streptopelia turtur) and the resident laughing dove (S. senegalensis), during spring, summer, and autumn. Wild birds were caught, treated with BrdU, and sacrificed five weeks later. New neurons were recorded in the hyperpallium apicale, hippocampus and nidopallium caudolateral regions. We found that in doves, unlike passerines, neuronal recruitment was lower in brains of the migratory species compared with the resident one. This might be due to the high sociality of doves, which forage and migrate in flocks, and therefore can rely on communal spatial knowledge that might enable a reduction in individual navigation efforts. This, in turn, might enable reduced levels of neuronal recruitment. Additionally, we found that unlike in passerines, seasonality does not affect neuronal recruitment in doves. This might be due to their non-territorial and explorative behavior, which exposes them to substantial spatial information all year round. Finally, we discuss the differences in neuronal recruitment between Columbiformes and Passeriformes and their possible evolutionary explanations. Our study emphasizes the need to further investigate this phenomenon in other avian orders and in additional species.